The dead family Diaz - Bracegirdle, P. J. (Dial Books for Young Readers, 2012)
Angelito Diaz is afraid of walking among the Living on the Day of the Dead, especially with his older sister, Estrellita, teasing him, but once in the Land of the Living, he quickly makes a new friend.